2019
DOI: 10.1521/aeap.2019.31.6.523
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and Mobile App Use Among Young Black Men Who Have Sex With Men

Abstract: INTRODUCTION: Young black men who have sex with men (YBMSM) are disproportionately affected by HIV. Intersectional stigmas are associated with increased HIV vulnerability, and worse outcomes for YBMSM with HIV. YBMSM find sex partners via sexual networking apps, but stigma on apps has been poorly studied. METHODS: We conducted cross-sectional analysis of 324 YBMSM seeking sex partners via apps to assess stigma experiences in eight dimensions compared to non-users (N=150). We conducted detailed stratified ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…HIV stigma-reduction approaches that harness technology to create online spaces where young Black sexual minority men could discuss HIV and sexuality stigma have been developed [ 74 , 75 ]. Considering the prominent role of online technologies in young men’s lives, interventions that reduce stigma on mobile health apps are needed [ 76 ]. Clinical trial tests of anti-HIV stigma approaches include a faith-based intervention for Black churches [ 77 79 ], a group-level intervention for Black women [ 80 ], and a community-level intervention for young Black men [ 81 , 82 ].…”
Section: Nih Icos With Hiv-related Stigma Research Approaches and Activitiesmentioning
confidence: 99%
“…HIV stigma-reduction approaches that harness technology to create online spaces where young Black sexual minority men could discuss HIV and sexuality stigma have been developed [ 74 , 75 ]. Considering the prominent role of online technologies in young men’s lives, interventions that reduce stigma on mobile health apps are needed [ 76 ]. Clinical trial tests of anti-HIV stigma approaches include a faith-based intervention for Black churches [ 77 79 ], a group-level intervention for Black women [ 80 ], and a community-level intervention for young Black men [ 81 , 82 ].…”
Section: Nih Icos With Hiv-related Stigma Research Approaches and Activitiesmentioning
confidence: 99%
“…Among the biased opinions against PLWH, health staff are less likely to stigmatize PLWH morally but more likely to be biased against them from a professional perspective [3,39,40]. PLWH is usually associated with the MSM, IDU and sexual workers, thus the general held the deep-rooted prejudice that HIV/AIDS is a punishment for their bad behavior [4,7]. A qualitative study conducted by Kriengkrai among Thai general population found that 38.2% would be ashamed of having a PLWH family member and 69.2% agreed that PLWH lose respect or standing [21].…”
Section: Biased Opinions Against Plwhmentioning
confidence: 99%
“…PLWH are often stigmatized as 'dirty' due to the fact that most commonly known transmission routes of HIV infection are commercial sex and injection drug use. Thus high-risk group like men who have sex with men (MSM), injection drug user (IDU), and sexual workers are also at high risk of being stigmatized or discriminated [4][5][6][7]. Studies suggested that compared to patients with other infectious disease like hepatitis B, victims of HIV infection are more likely to experience S&D from health care providers [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States (US), youth ages 13 to 24 years account for 22% of new HIV diagnoses (1), are the least likely group to be linked to care (2), and only 25% of youth with HIV attain an undetectable viral load (3). The reasons for poor health outcomes for youth with HIV (YHIV) and elevated HIV incidence among youth are multifactorial, but stigma plays a significant role (2,(4)(5)(6). Stigma occurs at all points along the continuum of HIV prevention and care, acting as a barrier to HIV testing (4), uptake of pre-exposure prophylaxis (PrEP) (7,8), linkage and retention in care (9), and adherence to antiretroviral therapy (ART) (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This ability to offer tailored intervention content is particularly important in the context of intersectional stigma. mHealth approaches can also overcome barriers to service utilization by reaching participants directly (6), increase access to affirming health information, foster social support and resilience (38), and provide structured, developmentallyappropriate tools for building healthy habits (e.g., providing daily reminders or goal-setting activities to support PrEP or ART adherence). Finally, it is relevant to note that many youth in the US experience social connectedness through mobile technologies (39), thus facilitating contact with peers who may be experiencing similar stigmas could provide new and meaningful social support.…”
Section: Introductionmentioning
confidence: 99%